3 - Inga et l'avenir industriel du Zaire - SHANKAMA, Alamumbul (Africa Development, 1981)
The author's contention in this article is that the Inga dam project of Zaïre will, as it is being implemented , serve more the interests of the developed countries involved in it than the native people of Zaïre. In his analysis he focuses on the prospects of an industrial development of Zaïre within the context of a full opemtion of this dam. He first looks into the Za ïrian industry as it is planned and as it is developing , then analyses the issue of energy which has been the main reason why this project was decided upon and finally looks at the industrial prospects of this country in terms of its advantages and foibles both at the internal as well as external level. In dealing with the first point of analysis, the author says that the zaïrian industry in its present form of development is characterized by a strong desire from the authorities to meet the needs of the investors toge- ther with those of the ruling classes by providing them with very cheap raw materials. This industry is fundamentally a dependent one and as such all the mecanisms for the accumulation and orientation of the generated surplus are distorted. As for the energy which is being produced by this dam, it is widening the already existing gap between the different parts of the country, mainly between the West (with a surplus of production) and the Shaba and Kivu regions ( with a deficit production ). This creates the paradoxical situa- tion that Zaïre is at the same time importing energy (from Zambia) and exporting it (to Congo). After looking at the different implications of the present form of industrialization of Zaïre with the energy produced by this dam, also after looking at the different directions which this industrialization can take, he concludes that whatever direction will be taken, the political and economic position of Zaïre as a sub-imperialist country within central Africa is clear and will with no doubt be reinforced because the country is granted with important assets such as an important and cheap energy production, important mineral as well as agricultural resources, an important potential market with possibilities of extension in the region, an abundant and cheap labour and also a strategic geopolitical position. Because of that position and because also of the nature of the different forms of industrialization envisaged, one can hardly expect Zavrian authorities to develop a genuine development strategy because they all are based on marginalization of the masses, social and regional inequity and the absence of an absolute break from imperialism.